Assessment of Attitudes, Knowledge and Practices of Medical Waste Management among Healthcare Workers in Blantyre Urban Health Centres - Libanga , Kenamu; Mzuza , Maureen Kapute (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
Health facilities generate extensive consignment of healthcare waste that may be hard to manage due to its ability to spread different infections if improperly handled. There is a need for healthcare workers who handles healthcare waste to have adequate knowledge and stick to proper healthcare waste management. This paper sought to assess knowledge, attitudes, and practices of medical waste Management among healthcare workers in selected health centres in Blantyre urban. A descriptive study design was deployed and analyse a study population comprising ten public health centres. Stratified random sampling was used where (n) = 81 healthcare workers from 10 health centres were interviewed. Data were collected using structured questionnaires, and Statistical Package for the Social Sciences was used in data analysis. The study revealed that knowledge of medical waste management could have been adequate, with 21% of the participants scoring below par. Some participants disclosed a good attitude towards healthcare waste management, though 31% revealed good practices. The study concludes that healthcare workers' knowledge, attitudes, and practices needed to be more satisfactory. Most health professionals could have performed better on the knowledge of healthcare waste management, which places healthcare workers, patients and the community around the health centre at risk. The researcher recommends that training, mentorship and supervision in healthcare waste management are needed as far as proper healthcare management is concerned.